HUBUNGAN STRES KERJA DENGAN SIKAP EMPATI PERAWAT MEDIKAL BEDAH RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2017 - Lilis Novitarum; Samfriati Sinurat; Marton Sianturi (STIKes Santa Elisabeth Medan, 2018)
Stress is the response of a person's body that is non-specific to any excessive workload demands. When a person is able to overcome the excessive burden and does not experience disruption of body function, then the person is not experiencing stress. empathy is the ability to understand what others feel and think which is the ability and skill in facilitating social agreements and successfully navigating personal relationships, it is important for the survival of individuals because it requires accuracy in the perception, interpretation, and response to the emotions of others. Therefore empathy is an important building block for prosocial behavior, or the actions of people taking other benefits. Goals : This study aims to analyze the relationship of nurses work stress with nurse empathy to patients in santa elisabeth field hospital in 2017. Methods : This study used cross-sectional approach with sampling total sampling technique, as many as 29 respondents. Result : Based on statistical test (chi-square) got p value = 0,006 (p <0,06) so there is significant relation between Work Stress With Empathy Attitude Medical Nurses Hospital Surgery Santa Elisabeth Medan Conclution : It is expected that the Hospital holds counseling or seminars on empathy and can give rewards in the form of materials such as praise or awards for nurses who have a sense of empathy. Medical Surgery Room at Santa Elisabeth Hospital Medan.